Respostas

2013-12-13T14:37:55-02:00
F(x) =  2x^{2}
g(x) = x + 1

Vamos resolver por partes!

- primeira parte:

g(2) = 2 + 1
g(2) = 3

f(2) = 2 . (2)²
f(2) = 2 . 4
f(2) = 8

- segunda parte:

f(g(2)) = f (3)
f(3) = 2 . (3)²
f(3) = 2 . 9
f(3) = 18

g(f(2)) = g (8)
g(2) = 8 + 1
g(2) = 9

- terceira parte:

f(g(2)) + g(f(2)) = f(3) + g(8) = 18 + 9 = 27

bom estudo! :)
3 5 3
2013-12-13T16:25:57-02:00
F(x) = 2x²
g(x) = x+1
g(2) = 2+1 = 3
f(g(2)) = f(3) = 2.3² = 2.9 = 18
f(2) = 2.2² = 2.4 = 8
g(f(2)) = g(8) = 8+1 =9

f(g(2)) + g(f(2)) = 18 + 9 = 27

2 4 2